Surface arrangement dependent selectivity of porphyrins gas sensors - Magna, Gabriele; Zor, Sule Dinc; Catini, Alexandro; Capuano, Rosamaria; Basoli, Francesco; Martinelli, Eugenio; Paolesse, Roberto; Di Natale, Corrado (ELSEVIER SCIENCE SA, 2017)
Optimal design of sensor arrays requires the control of selectivity of each sensor elements. To this regard, porphyrins are a versatile molecular platform, whose selectivity can be changed with a suitable synthesis. Besides the molecular structure, the sensor properties are also influenced by the mutual arrangement of porphyrins onto the sensor surface. To take advantage of this additional feature we considered porphyrins coated ZnO nanoparticles prepared following two methods In the former, porphyrins coat the surface of ZnO nanoparticles previously grown by hydrothermal route, while the second method is a one-pot synthesis where porphyrins are added to the nanoparticles precursor solution. The two approaches lead to different morphologies evidenced by the shape of the oxide nanoparticles. In order to consider the whole range of interactions with airborne chemicals, mass transducers, such as quartz microbalances, have been used to prepare sensors. Results show that besides morphology, the material preparation has an impact on the selectivity and the sensitivity, and these differences are enough to discriminate volatile compounds both as individual or complex blends. This is demonstrated by a minimal array made of three sensors based on the same porphyrin, but on different surfaces (QMB electrode gold and two differently prepared ZnO structures), applied in a simple electronic nose application aimed at identifying two different cultured cells. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Porphyrins; ZnO nanoparticles; Quartz microbalance; Sensor array; EXHALED BREATH; ZNO NANORODS; Chemistry; Electrochemistry; Instruments & Instrumentation